Understanding Societal Resilience—Cross-Sectional Study in Eight Countries - Bodas, Moran; Peleg, Kobi; Stolero, Nathan; Adini, Bruria (Frontiers in Public Health, 2022)
Civilian populations that are more prepared for emergencies are more resilient. Ample research has been carried out over the last three decades to identify the factors that contribute to public readiness to emergencies and disasters and enhance societal resilience. However, the analysis did not achieve an in-depth comprehension of the types of contributing factors, namely, contextual vs. target aspects. A cross-sectional study that explored attitudinal factors among civilian populations took place during the months of January–February 2021. Diverse representative samples (N ≥ 500 each) of adults from eight countries (Italy, Romania, Spain, France, Sweden, Norway, Israel, and Japan) were engaged. The primary outcomes of this study were individual and societal resilience as well as emergency preparedness. The results suggest that in most countries, levels of trust are relatively high for emergency services and health services, and relatively low for politicians. In the overall sample, the individual preparedness index, which delineates the compliance with general household adjustment recommendation for emergencies, averaged at 4.44 ± 2.05SD (out of 8). Some variability was observed between countries, with some countries (e.g., Spain, Norway, and Italy) reporting higher preparedness rates than others (e.g., Japan). In the overall sample, levels of individual resilience were mediocre. Multivariate analysis showed that the following variables are predictors of societal resilience: trust (β = 0.59), social norms and communality (β = 0.20), individual resilience (β = 0.05), individual preparedness (β = 0.04), risk awareness (β = 0.04), and age (β = 0.03). The results of this study show that there are commonalities and differences between societies across Europe and beyond concerning societal resilience at large, including preparedness, individual resilience, and risk perception. Despite socio-cultural driven differences, this study shows that societies share varied characteristics that may contribute toward a common model for assessing societal resilience and for explaining and predicting resilience and readiness.